Hypergammaglobulinemia in treated and untreated people with HIV - Isabel Vigmo; Staffan Nilsson; Aylin Yilmaz; Magnus Gisslén; Josefina Robertson; Johanna Karlsson (PLoS ONE, 2026)
Background B cell abnormalities are an early feature of human immunodeficiency virus-1 (HIV) infection, leading to hypergammaglobulinemia. Objective(s) The aim of this study was to evaluate serum levels of immunoglobulin G (IgG) as well as the inflammatory biomarkers neopterin, β2-microglobulin and albumin in a large cohort of untreated as well as virologically suppressed people with HIV (PWH) on antiretroviral therapy (ART). Methods We conducted a cross-sectional analysis of blood samples from untreated PWH and virologically suppressed participants on ART. Of 750 collected blood samples, 267 were from ART-suppressed participants and 483 from untreated participants. Levels of IgG, HIV-RNA, CD4 + T cells, β2-microglobulin, neopterin and albumin were analyzed with regard to age, sex and stage of HIV infection. Results Hypergammaglobulinemia was present in all subgroups of untreated PWH except in those with primary HIV infection. Participants with a CD4 + T cell count between 50 and 349 cells/µL exhibited the highest IgG concentrations. Elevated IgG concentrations prevailed in 24% of participants on ART. Serum neopterin and β2-microglobulin levels were significantly elevated in untreated PWH. They decreased in participants on ART, but remained abnormally elevated in approximately half of those. Conclusion Although IgG levels were normalized in a majority of participants on ART, hypergammaglobulinemia prevailed in about a quarter of cases, indicating a remaining B cell hyperactivity despite viral suppression. The finding of elevated levels of inflammatory biomarkers despite ART suppression is suggestive of residual inflammatory activity and parallels the finding of persisting hypergammaglobulinemia.